Unintended consequences: DAC governments and shrinking civil society space in Kenya. Issue 5 (3rd July 2016) - Wood, Jacqueline
ABSTRACT: In the post-Cold War era, rights and democracy promotion became a significant component of Western governments' developing country engagement, including through CSOs. Today, a backlash against CSOs is evident in many developing countries. Drawing from interviews in Kenya, this article reflects on the potential unintended consequences of Western government actions that may be contributing to the backlash, undermining the sustainability of rights and democracy gains, and of CSOs. Autocratic leaders' hostility toward reformist voices; counter-terrorism and security; emphasis on the private sector and trade; and modalities of CSO support, all suggest the need for careful consideration of Western governments' actions.